Dietary and phytogenic inclusion effects on the broiler chicken cecal ecosystem - Palamidi, Irida; Paraskeuas, Vasileios V.; Mountzouris, Konstantinos C. (Frontiers in Animal Science, 2023)
Dietary modulation in broilers is crucial for the establishment of a beneficial microbiota and subsequently the promotion of intestinal health. In this trial, a 2 × 2 factorial design with two different specifications with respect to the dietary metabolizable energy (ME) and crude protein (CP) levels (i.e., 95and 100% of recommendations) and two levels of phytobiotic (0 and 150 mg/kg diet), were used. Total bacteria, Bacteroides spp, Lactobacillus spp and Clostridium cluster XIVa levels attached to the cecal mucosa and Clostridium cluster XIVa in the cecal digesta, as well as the molar ratio of butyric acid were lower in broilers fed the 95% ME and CP specification diets. In addition, the relative activity of autoinducers-2 (AI-2) and the expression levels of TLR4 and AvBD6 were increased. Phytobiotic supplementation reduced cecal digesta E. coli and Clostridium cluster I levels and increased the Clostridium cluster IV. Moreover, the butyric acid molar ratio and the relative activity of AI-2 were increased, whereas the branched VFA and the AvBD6 and LEAP2 expressions were reduced by phytobiotic administration. Dietary specifications and phytobiotic interactions were shown for the cecal attached microbiota composition, metabolic activity of digesta microbiota, relative expression of autoinducers-2 and relative expression of toll-like signaling molecules and host antimicrobial peptides. In conclusion, it has been shown that ME and CP dietary specifications combined or not with phytobiotic modulate multilevel gut biomarkers starting from microbiota composition and metabolic activity to microbial communications and host signaling to inflammation and defense.